2020
DOI: 10.21508/1027-4065-2020-65-3-131-137
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric sepsis – time to reach agreement

Abstract: Objective: to present the evolution and modern concept of pediatric sepsis.According to many authors, pediatric sepsis is considered to be the main cause of death from infectious diseases; and the mortality is associated with a late diagnosis and non-compliance with treatment guidelines. The article discusses the evolution of views on sepsis over the past 30 years. It analyzes the changes of sepsis concepts in adults from Sepsis-1 to Sepsis-3. Currently, sepsis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…According to international protocols [23][24][25][26][27][28][29][30][31], confirmed sepsis / SS requires rapid provision of venous access and initiation of infusion (vasopressors, if necessary), administration of antibiotics 1-3 hours before sampling for microbiological examination. Studies have shown a correlation between increased mortality and delayed ABT prescription after sepsis / SS is identified.…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…According to international protocols [23][24][25][26][27][28][29][30][31], confirmed sepsis / SS requires rapid provision of venous access and initiation of infusion (vasopressors, if necessary), administration of antibiotics 1-3 hours before sampling for microbiological examination. Studies have shown a correlation between increased mortality and delayed ABT prescription after sepsis / SS is identified.…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%